2011
DOI: 10.1039/c0cc03821k
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic hydrogenation of graphene films

Abstract: We developed a novel and facile method to hydrogenate graphene by using a conditioning catalyst upstream of the graphene sample to generate atomic hydrogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 16 publications
3
31
0
Order By: Relevance
“…Even if various studies based on calculations hypothesized that diamane can form when nonsupported 2LG and 3LG are placed in hydrogen cold plasma, to the best of authors' knowledge, there is no report of any experimental evidence of such scenario. Only few experimental studies on the hydrogenation of FLG have been published [19,26,27,28,29]. In particular, no features from diamane were reported in Raman spectra.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if various studies based on calculations hypothesized that diamane can form when nonsupported 2LG and 3LG are placed in hydrogen cold plasma, to the best of authors' knowledge, there is no report of any experimental evidence of such scenario. Only few experimental studies on the hydrogenation of FLG have been published [19,26,27,28,29]. In particular, no features from diamane were reported in Raman spectra.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, since the first experimental description of hydrogenated 1LG and 2LG [32], only few experimental studies and methods were reported on this topic. Those methods have been mainly focusing on two approaches: gas phase [19,26,27,29,33,34,35,36,37,38,39,40] or liquid phase hydrogenation [41,42,43,44,45,46]. A review on the subject is available in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…No such groups are detected for the silver-modified copper sample. Reportedly, -CH n groups are one type of the most efficient surface energy reductants which could make the surface water repellent, 21,22 directly inducing the hydrophobic behavior, given the proper chemical composition.…”
Section: Resultsmentioning
confidence: 99%
“…The efficient hydrogenation of graphene can also be possible by catalytic conversion where catalyst provides a new reduction pathway of graphene through dissociation of graphene molecule [63]. The intercalated Ni nanoparticles inside of the alumina matrix with the flow of H2 at 820°C demonstrated the catalytic hydrogenation of graphene films (Fig.17).…”
Section: Graphene and Graphanementioning
confidence: 99%